High-hardness nickel imprint template based on nanostructure reshaping and preparation method of high-hardness nickel imprint template

By preparing high-hardness nickel imprint templates, the problems of low hardness and short service life of nanotemplates were solved, realizing high-precision and low-cost large-scale micro-nano structure replication, which is suitable for industrial applications of metasurfaces and micro-nano optical devices.

CN121084045APending Publication Date: 2025-12-09HARBIN ENGINEERING UNIVERSITY SANYA NANHAI INNOVATION & DEVELOPMENT BASE +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511279198.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing nanotemplates suffer from low hardness, short lifespan, low replication accuracy, and complex fabrication processes, making it difficult to achieve low-cost, high-precision, and large-scale production of highly conformable micro- and nanostructures.

Method used

A method for preparing a high-hardness nickel imprint template based on nanostructure reshaping is adopted, which includes steps such as aluminum sheet pretreatment, nanoimprinting, anodizing, gradient concentration PMMA spin coating, chemical etching, and electrochemical nickel plating to form a high-hardness nickel imprint template.

Benefits of technology

It achieves high-precision, low-cost, and reliable micro/nano structure replication, significantly improves template hardness, extends service life, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121084045A_ABST
    Figure CN121084045A_ABST
Patent Text Reader

Abstract

The invention discloses a high-hardness nickel imprinting template based on nanostructure reshaping and a preparation method of the high-hardness nickel imprinting template, and belongs to the technical field of nanostructure machining.The preparation method of the high-hardness nickel imprinting template comprises the following steps that a PMMA solution with gradient concentration is adopted for conducting spin coating on a mother-structure aluminum cone for multiple times, gaps of the aluminum cone are completely filled, and the mother-structure aluminum cone is obtained; forming a PMMA complementary structure complementary with the mother structure aluminum cone; a mother structure aluminum cone is thoroughly removed through a chemical corrosion method, and a PMMA complementary structure is reserved; plating a silver layer on the surface of the PMMA complementary structure by adopting a magnetron sputtering method to obtain a PMMA complementary structure coated with the silver layer; the PMMA complementary structure coated with the silver layer is placed in nickel deposition liquid to be subjected to electrochemical nickel plating, and a nickel layer is formed; pMMA is removed through a dissolution method, and the high-hardness nickel imprinting template is obtained. The preparation method is high in reshaping precision, the complex nanometer morphology can be accurately copied, the hardness of the prepared nickel imprinting template is remarkably improved, and the nickel imprinting template can bear imprinting for at least hundreds of times without obvious abrasion deformation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanostructure processing technology, specifically a high-hardness nickel imprint template based on nanostructure replication and its preparation method. Background Technology

[0002] In today's micro-nano fabrication field, as electronic devices continue to develop towards miniaturization and high performance, the requirements for the precision and quality of micro-nano structures have reached unprecedented heights. The fabrication methods for micro-nano structures are the core technologies for achieving precise manufacturing at the micro-nano scale. Currently, the fabrication of micro-nano structure replicas mainly relies on high-precision micro-nano fabrication technologies such as focused ion beam etching (FIB), multiphoton laser direct writing (MPL), and nanoimprint lithography (NIL).

[0003] These technologies have propelled micro- and nanofabrication from the laboratory to industrialization over the past two decades: focused ion beam etching enables sub-10nm cutting and repair, providing strong support for chip defect repair and the construction of three-dimensional nanostructures; multiphoton laser direct writing, with its excellent three-dimensional processing capabilities, can write arbitrary topological structures in three-dimensional space in a single stroke, demonstrating significant advantages in the fabrication of biological scaffolds and microfluidic chips; and nanoimprint lithography, with its high-efficiency, low-cost mass production potential, has become a popular choice for large-scale fabrication of nanopatterns. These technologies collectively drive the continuous progress of the micro- and nanofabrication industry.

[0004] Although these methods can achieve the fabrication of complex structures at nanoscale resolution, they still have significant limitations in practical applications: 1. High equipment and process costs: Technologies such as FIB and MPL rely on precision instruments (such as high-energy ion beams or femtosecond laser systems), which have extremely high equipment purchase and maintenance costs and low processing efficiency, making it difficult to meet the needs of large-scale production.

[0005] 2. High process complexity: Nanoimprint lithography has high throughput potential, but template preparation relies on electron beam lithography (EBL) or deep ultraviolet lithography (DUV). The process steps are complex and easily affected by template wear and demolding defects, which leads to a decrease in yield.

[0006] 3. Limited fabrication of three-dimensional and multi-scale structures: Traditional photolithography techniques (such as ultraviolet lithography and electron beam lithography) are relatively mature in two-dimensional patterning, but they still face challenges in the precise control of complex three-dimensional structures or multi-scale complexes, making it difficult to achieve large-scale fabrication with high conformability and high consistency.

[0007] 4. Insufficient material compatibility and performance control: Existing technologies have varying applicability to different functional materials (such as metals, dielectrics, polymers, etc.), and factors such as thermal effects and mechanical stress during processing may lead to deviations in structural morphology, thereby affecting key performance characteristics of micro-nano complex devices such as electromagnetic response, plasmon coupling, and photon localization.

[0008] Furthermore, existing nanotemplates suffer from problems such as low hardness, short lifespan, low replication accuracy, and complex fabrication processes. If replicating nanostructures with specific shapes is required, photolithography technology is necessary, which involves expensive equipment and complex processes. Therefore, developing a low-cost, high-precision, and high-throughput micro / nano replication fabrication technology to overcome the bottlenecks of existing processes in low-cost, large-scale production, and high-precision three-dimensional conformal fabrication is of great significance for promoting the industrial application of metasurfaces, micro / nano optical devices, and biosensors. Summary of the Invention

[0009] The purpose of this invention is to provide a method for preparing a high-hardness nickel imprint template based on nanostructured composites, so as to solve the problems mentioned in the background art.

[0010] To achieve the above objectives, the embodiments of the present invention provide the following technical solutions: A method for preparing a high-hardness nickel imprint template based on a nanostructured composite includes the following steps: The surface of the aluminum sheet is pretreated to obtain a smooth aluminum substrate. Nanoimprinting is performed on an aluminum substrate to form hexagonal nano-depressions, and then the substrate is placed in a first electrolyte for anodic oxidation to obtain a micro-nano structure with an oxide layer. The oxide layer of the micro / nano structure is removed to obtain the parent aluminum cone structure; The parent aluminum cone was spin-coated multiple times with a PMMA solution of gradient concentration to completely fill the gaps between the aluminum cones, forming a PMMA complementary structure that is complementary to the parent aluminum cone. The parent aluminum cone structure was completely removed by chemical etching, while the PMMA complementary structure was preserved. A silver layer was deposited on the surface of a PMMA complementary structure using magnetron sputtering to obtain a PMMA complementary structure coated with a silver layer. A silver-coated PMMA complementary structure was placed in a nickel deposition solution for electrochemical nickel plating to form a nickel layer, thus obtaining a nickel-complementary structure composite. High-hardness nickel imprinting templates were obtained by removing PMMA from nickel-complementary structure complexes through a dissolution method.

[0011] Furthermore, the pretreatment step for the surface of the aluminum sheet specifically includes: An aluminum sheet was subjected to ultrasonic treatment by sequentially placing it in anhydrous ethanol, ultrapure water, and anhydrous ethanol. Subsequently, the aluminum sheet was polished electrochemically in a second electrolyte. The aluminum sheet was then removed and rinsed with anhydrous ethanol and ultrapure water to obtain a smooth aluminum substrate. The second electrolyte included perchloric acid and ethanol.

[0012] Furthermore, the first electrolyte includes phosphoric acid, ethylene glycol, and ultrapure water.

[0013] Furthermore, the method for removing the oxide layer of the micro / nano structure is to use chromic acid solution for etching.

[0014] Furthermore, the PMMA solution is a dichloromethane solution of polymethyl methacrylate; first, spin coating is performed using a PMMA solution with a concentration of 0.01-0.04 g / mL, and then spin coating is performed using a PMMA solution with a concentration of 0.045-0.08 g / mL.

[0015] Furthermore, the steps for completely removing the parent aluminum cone structure using chemical etching specifically include: The parent aluminum cone structure was placed bottom-down in a mixture of hydrochloric acid and copper chloride for etching. It was then transferred to a copper chloride solution to completely remove the parent aluminum cone structure, leaving only the PMMA complementary structure.

[0016] Furthermore, the step of electrochemically plating nickel in a nickel deposition solution using a silver-coated PMMA complementary structure specifically includes: A silver-coated PMMA complementary structure was placed in a nickel deposition solution and electrochemically nickel was plated in three stages: the first stage was performed with an oxidation current of 1-2 mA for 0.5-1.5 h; the second stage was performed with an oxidation current of 2.5-3.5 mA for 1-3 h; and the third stage was performed with an oxidation current of 4-6 mA for 1-3 h. After the three stages, a uniform nickel layer was deposited on the surface of the silver-coated PMMA complementary structure. This nickel layer was tightly bonded to the structure, forming a nickel-complementary structure composite.

[0017] Furthermore, the nickel deposition solution includes nickel sulfate hexahydrate, nickel chloride hexahydrate, and boric acid.

[0018] Another object of the present invention is to provide a high-hardness nickel embossing template prepared by the above-described preparation method.

[0019] Another objective of this invention is to provide an application of the above-mentioned high-hardness nickel imprint template in nanoimprinting and micro / nano device fabrication.

[0020] This invention provides a method for preparing a high-hardness nickel imprint template based on nanostructure replication. The method utilizes an aluminum cone structure replication to prepare the nickel imprint template, combining nanoimprinting and electrochemical deposition processes. This provides an effective solution for the mass production of low-cost, high-hardness, and highly consistent micro / nano structures. The preparation method provided by this invention offers high replication accuracy, precisely replicating complex nanomorphologies to meet high-precision replication requirements. Furthermore, the process is simple, efficient, has a short preparation cycle, is easy to control, and facilitates standardized production. The hardness of the obtained nickel imprint template is significantly improved, capable of withstanding at least several hundred imprint cycles without significant wear or deformation. Attached Figure Description

[0021] Figure 1 A schematic diagram of the fabrication process for the parent structure aluminum cone.

[0022] Figure 2 The top view (left) and SEM image (right) of the basic morphology of the parent aluminum cone structure are shown.

[0023] Figure 3 The left image shows a side view of the basic morphology of the parent aluminum cone structure, and the right image shows a SEM image.

[0024] Figure 4 A schematic diagram of the process for reshaping the parent aluminum cone structure.

[0025] Figure 5 The images show a schematic diagram (left) and a SEM image (right) of the basic morphology of the high-hardness nickel imprint template prepared according to an embodiment of the present invention.

[0026] Figure 6 This is a diagram showing the effect of the high-hardness nickel embossing template obtained in an embodiment of the present invention after embossing.

[0027] Figure 7 This is a SEM image of the high-hardness nickel embossing template obtained in an embodiment of the present invention after 10 embossing cycles.

[0028] In the figure: 1-aluminum sheet; 2-aluminum substrate; 3-nickel template; 4-imprinted substrate; 5-oxide layer; 6-aluminum cone; 7-PMMA complementary structure; 8-silver layer; 9-nickel layer; 10-nickel imprinting template. Detailed Implementation

[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0030] In order to overcome the problems of low hardness, short service life, low replication accuracy and complex preparation process of existing nanotemplates, this invention provides a high-hardness nickel imprint template based on nanostructure replication. This template achieves accurate replication of the original nanostructure, ensures that the nickel template is highly consistent with the parent structure to meet the replication accuracy requirements, and significantly improves the template hardness to extend service life and reduce production costs.

[0031] Specifically, such as Figure 1 and Figure 4 As shown, in one embodiment of the present invention, a method for preparing a high-hardness nickel imprint template based on a nanostructured composite is provided, comprising the following steps: S1. Pre-treatment of the surface of aluminum sheet 1: The aluminum sheet 1 is placed in anhydrous ethanol, ultrapure water and anhydrous ethanol in sequence for ultrasonic treatment. Then, it is placed in the second electrolyte and polished by electrochemical method. Then, the aluminum sheet 1 is taken out and rinsed with anhydrous ethanol and ultrapure water in sequence to obtain a smooth aluminum substrate 2. The second electrolyte is prepared by mixing perchloric acid and ethanol in a volume ratio of (0.5-1.5):(6-8).

[0032] S2. Aluminum substrate 2 is nanoimprinted using a nickel template 3 with a hexagonal close-packed structure to form hexagonal nano-depressions, resulting in imprinted substrate 4. Then, imprinted substrate 4 is placed in a first electrolyte for anodic oxidation to obtain a micro / nano structure with an oxide layer 5. The first electrolyte is prepared by mixing phosphoric acid, ethylene glycol, and ultrapure water in a mass ratio of 1:(150-250):(350-450).

[0033] S3. The oxide layer 5 of the micro-nano structure is removed by etching with chromic acid solution to obtain the parent structure aluminum cone 6.

[0034] S4. The parent aluminum cone 6 is spin-coated multiple times with PMMA (polymethyl methacrylate) solutions of varying concentrations. Specifically, a PMMA solution with a concentration of 0.01-0.04 g / mL is first used for spin-coating, followed by a PMMA solution with a concentration of 0.045-0.08 g / mL, so that the PMMA completely fills the gaps between the aluminum cones 6, forming a PMMA complementary structure 7 that is complementary to the parent aluminum cone structure. The PMMA solution is a dichloromethane solution of polymethyl methacrylate (PMMA).

[0035] S5. Thoroughly remove the parent structure aluminum cone 6 by chemical etching: After PMMA has cured, place the parent structure aluminum cone 6 bottom-down into a hydrochloric acid-copper chloride mixed solution (prepared by dissolving 3-5g of copper chloride dihydrate in 80-120mL of hydrochloric acid and 80-120mL of ultrapure water) for etching treatment. Then transfer it to a copper chloride solution (prepared by dissolving 3-5g of copper chloride dihydrate in 200mL of ultrapure water) to thoroughly remove the parent structure aluminum cone 6, leaving only the PMMA complementary structure 7. At this time, the PMMA complementary structure 7 completely retains the negative characteristics of the parent structure.

[0036] S6. A 20-40 nm thick silver layer 8 is deposited on the surface of the PMMA complementary structure 7 using magnetron sputtering to obtain the PMMA complementary structure 7 covered with the silver layer 8.

[0037] S7. Place the PMMA complementary structure 7 coated with silver layer 8 in a nickel deposition solution and perform electrochemical nickel plating in three stages: the first stage is to pass an oxidation current of 1-2 mA for 0.5-1.5 h; the second stage is to pass an oxidation current of 2.5-3.5 mA for 1-3 h; and the third stage is to pass an oxidation current of 4-6 mA for 1-3 h. After the three stages are completed, a uniform nickel layer 9 is deposited on the surface of the PMMA complementary structure 7 coated with silver layer 8. The nickel layer 9 is tightly bonded to the structure to form a nickel-complementary structure composite. The nickel deposition solution includes nickel sulfate hexahydrate, nickel chloride hexahydrate, and boric acid in a mass ratio of (35-40):(10-15):(4-6). The solvent used in the nickel deposition solution can be, but is not limited to, water. The amount of solvent is not limited and can be used to dissolve or disperse nickel sulfate hexahydrate, nickel chloride hexahydrate, and boric acid.

[0038] S8. High-hardness nickel imprinting template 10 can be obtained by removing PMMA from the nickel-complementary structure complex using an acetone solution via a dissolution method. It should be noted that the concentration of the acetone solution is not limited, as long as it can completely dissolve the PMMA.

[0039] In practical applications, the morphology monitoring of aluminum cone 6 after deoxidation is as follows: after chromic acid etching, 5 points are randomly selected by SEM every 1 hour. Etching is stopped when the cone tip curvature radius is ≤15nm and the sidewall perpendicularity is ≥89° to prevent excessive etching from causing the cone tip to collapse.

[0040] In this embodiment of the invention, the gradient PMMA spin-coating process solves the problem of replicating high aspect ratio structures. Complete filling of high aspect ratio structures is a key technical challenge in the replication of micro / nano structures. Traditional single-concentration PMMA spin-coating easily leads to incomplete filling and uneven surface. This embodiment of the invention adopts a "low concentration → high concentration" gradient spin-coating strategy to achieve perfect structural filling and mechanical strengthening in stages: the low-viscosity solution rapidly penetrates to the bottom of the nanostructure through capillary forces; three spin-coatings ensure the removal of residual air bubbles layer by layer; and the higher viscosity fills the microscopic defects of the initial spin-coating, increasing the PMMA film thickness and improving the mechanical strength of subsequent structures.

[0041] This invention employs a three-stage electrochemical nickel plating process. A PMMA complementary structure 7 coated with a silver layer 8 is placed in a nickel deposition solution, and electrochemical nickel plating is performed in three stages. In the first stage, a low current is applied to induce uniform nucleation, forming dense nanocrystal nuclei on the surface of the silver layer 8. In the second stage, a moderate current is applied to accelerate deposition, filling the gaps in the PMMA structure. The gradient current design avoids edge effects caused by high current, enabling precise replication of a 100nm linewidth. After the three stages, a uniform nickel layer 9 is deposited on the structure surface. This nickel layer 9 is tightly bonded to the structure, forming a nickel-complementary structure composite.

[0042] In addition, the preparation method provided in this embodiment of the invention can be dynamically adjusted to adapt to micro and nano structures of different scales and morphologies: PMMA spin coating can maintain the core strategy of "low concentration → high concentration" of gradient spin coating, and only the concentration gradient of PMMA solution and spin coating speed need to be adjusted; for irregular curved surface structures such as spherical and conical surfaces, the three-stage current gradient and time can be changed according to the micro and nano structure during the nickel plating stage, and the slow current increase characteristic can be used to adapt to the curvature change of the curved surface, avoiding excessive local deposition.

[0043] The following embodiments are specific implementations of the present invention in practical applications, but are not limited thereto.

[0044] Example: Figure 1 and Figure 4 As shown, this embodiment provides a method for preparing a high-hardness nickel imprint template based on a nanostructured composite, including the following steps: S1. Pretreatment of the surface of aluminum sheet 1: High-purity aluminum foil with a purity ≥ 99.99% is used and cut into circular aluminum sheets 1 with a diameter of 2cm. The aluminum sheet 1 is placed in a small beaker containing anhydrous ethanol, ultrapure water and anhydrous ethanol in sequence for ultrasonic treatment for 7 minutes. After that, it is taken out and dried. Then, it is placed in the second electrolyte and polished by electrochemical method. The 4℃ ice water bath is maintained. During the ice water bath, a constant voltage of 30V and a current limit of 2A are applied. After 6.5 minutes, the power is turned off. Then, the aluminum sheet 1 is taken out and rinsed with anhydrous ethanol and ultrapure water in sequence to obtain a smooth aluminum substrate 2. The second electrolyte is prepared by mixing perchloric acid and ethanol in a volume ratio of 1:7.

[0045] S2. A nickel template 3 with a hexagonal close-packed structure and a period of 400 nm is placed on an aluminum substrate 2. A pressure of 5 MPa is applied using a hydraulic press and held for 2 minutes to perform nanoimprinting on the aluminum substrate 2, forming hexagonal 400 nm nano-depressions, resulting in an imprinted substrate 4. The imprinted substrate 4 is then placed in a first electrolyte at 4 °C for anodic oxidation (with a constant voltage of 160 V, a current limit of 0.03 A, and continuous oxidation for 1 hour) to obtain a micro / nano structure with an oxide layer 5. The first electrolyte is prepared by mixing phosphoric acid, ethylene glycol, and ultrapure water in a mass ratio of 1:200:400.

[0046] S3. The oxide layer 5 of the micro / nano structure is removed by etching with chromic acid solution, and the structure is soaked for at least 6 hours to obtain the parent aluminum cone 6. The basic morphology schematic diagram and SEM image of the cone 6 from different perspectives are shown below. Figure 2 and Figure 3 As shown.

[0047] S4. The parent structure aluminum cone 6 is spin-coated multiple times using PMMA solutions of varying concentrations. Specifically, the initial spin-coating involves adding 450 μL of polymethyl methacrylate (0.5 g PMMA powder dissolved in 15 mL dichloromethane) to the surface of the aluminum cone 6, using a spin coater with a speed of 180 r / min and a time of 15-20 s, and repeating this process three times. Subsequently, an enhanced spin-coating is performed by spin-coating 450 μL of a more concentrated PMMA solution (1 g PMMA powder dissolved in 20 mL dichloromethane) onto the aluminum cone 6 using the same parameters. This ensures that the PMMA completely fills the gaps in the aluminum cone 6, eliminates bubble defects, and forms a PMMA complementary structure 7 that is complementary to the parent structure aluminum cone 6.

[0048] S5. Thoroughly remove the parent structure aluminum cone 6 by chemical etching: After PMMA has cured, place the parent structure aluminum cone 6 bottom-down into a mixed solution of hydrochloric acid and copper chloride (prepared by dissolving 3.4g of copper chloride dihydrate in 100mL of hydrochloric acid and 100mL of ultrapure water) for etching treatment. When the aluminum cone 6 is about to be completely etched, transfer it to a copper chloride solution (prepared by dissolving 3.4g of copper chloride dihydrate in 200mL of ultrapure water) to thoroughly remove the parent structure aluminum cone 6, leaving only the PMMA complementary structure 7.

[0049] S6. A 30 nm thick silver layer 8 is deposited on the surface of the PMMA complementary structure 7 using magnetron sputtering to obtain the PMMA complementary structure 7 covered with the silver layer 8.

[0050] S7. The PMMA complementary structure 7 coated with silver layer 8 is placed in a nickel deposition solution (the mass ratio of nickel sulfate hexahydrate, nickel chloride hexahydrate, and boric acid is 38:12:5), and electrochemical nickel plating is performed in three stages: the first stage is with an oxidation current of 1.5 mA for 1 hour; the second stage is with an oxidation current of 3.0 mA for 2 hours; and the third stage is with an oxidation current of 5.0 mA for 2 hours. After the three stages are completed, a uniform nickel layer 9 is deposited on the surface of the PMMA complementary structure 7 coated with silver layer 8. The nickel layer 9 is tightly bonded to the structure to form a nickel-complementary structure composite.

[0051] S8. PMMA in the nickel-complementary structure complex was removed by dissolution with acetone solution to obtain a high-hardness nickel imprint template 10, which is a complex structure that precisely corresponds to the original parent structure. Its basic morphology schematic diagram and SEM image are shown below. Figure 5 As shown in the SEM image, the nickel embossing template 10 prepared in this embodiment of the invention maintains a high degree of consistency with the parent structure, achieving a "precise replication" effect, and this nickel embossing template can be used for the next embossing step.

[0052] Abrasion resistance test: The nickel embossing template 10 prepared in the above embodiment was subjected to a reciprocating embossing abrasion test. The embossing pressure was 5 MPa, and the embossing effect was as follows. Figure 6 As shown, the template morphology was inspected after ten imprints, as follows: Figure 7 As shown in the figure, the nickel imprint template 10 prepared in this embodiment of the invention exhibits high stability, showing no significant wear or deformation even after multiple imprinting processes. The experimental data above demonstrate, from both dimensional accuracy and wear resistance perspectives, that the preparation method provided in this embodiment of the invention possesses the core advantages of "high replication accuracy and good stability."

[0053] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification.

Claims

1. A method for preparing a nanostructure-replicated high-hardness nickel imprint template, characterized by, The method comprises the following steps: a surface of an aluminum sheet is pretreated to obtain a smooth aluminum substrate; the aluminum substrate is nanoimprinted to form a hexagonal array of nano-recesses, and then is subjected to anodic oxidation in a first electrolyte to obtain a micro-nano structure with an oxide layer; the oxide layer of the micro-nano structure is removed to obtain a mother structure aluminum cone; a gradient concentration PMMA solution is used to spin coat the mother structure aluminum cone for multiple times to completely fill the gaps between the aluminum cones and form a PMMA complementary structure complementary to the mother structure aluminum cone; the mother structure aluminum cone is completely removed by a chemical etching method to leave the PMMA complementary structure; a silver layer is plated on the surface of the PMMA complementary structure by a magnetron sputtering method to obtain the PMMA complementary structure with the silver layer; the PMMA complementary structure with the silver layer is subjected to electrochemical nickel plating in a nickel deposition solution to form a nickel layer and obtain a nickel-complementary structure composite; the PMMA in the nickel-complementary structure composite is removed by a dissolving method to obtain a high-hardness nickel imprinting mold.

2. The method of claim 1, wherein the nanostructure-based high-hardness nickel imprint template is prepared by the steps of: (a) preparing a nickel film on a substrate; (b) preparing a nanostructure on the nickel film; (c) preparing a nanostructure-based high-hardness nickel imprint template by etching the nickel film. The step of pretreating the surface of the aluminum sheet specifically comprises: the aluminum sheet is sequentially subjected to ultrasonic treatment in anhydrous ethanol, ultrapure water and anhydrous ethanol, and then is polished in an electrochemical manner in a second electrolyte, and then is taken out and sequentially washed with anhydrous ethanol and ultrapure water to obtain the smooth aluminum substrate; the second electrolyte comprises perchloric acid and ethanol.

3. The method for preparing a high-hardness nickel imprint template based on a nanostructured composite according to claim 1, characterized in that, The first electrolyte comprises phosphoric acid, ethylene glycol and ultrapure water.

4. The method for preparing a high-hardness nickel imprint template based on a nanostructured composite according to claim 1, characterized in that, The method for removing the oxide layer of the micro-nano structure is etching with a chromic acid solution.

5. The method for preparing a high-hardness nickel imprint template based on a nanostructured composite according to claim 1, characterized in that, The PMMA solution is a dichloromethane solution of polymethyl methacrylate; the spin coating is first performed with a PMMA solution with a concentration of 0.01-0.04 g / mL, and then is performed with a PMMA solution with a concentration of 0.045-0.08 g / mL.

6. The method for preparing a high-hardness nickel imprint template based on a nanostructured composite according to claim 1, characterized in that, The step of completely removing the mother structure aluminum cone by a chemical etching method specifically comprises: the bottom surface of the mother structure aluminum cone is placed in a mixed copper chloride hydrochloride solution for etching treatment, and then is transferred to a copper chloride solution to completely remove the mother structure aluminum cone and leave only the PMMA complementary structure.

7. The method for preparing a high-hardness nickel imprint template based on a nanostructured composite according to claim 1, characterized in that, The step of placing the PMMA complementary structure with the silver layer in a nickel deposition solution for electrochemical nickel plating specifically comprises: the PMMA complementary structure with the silver layer is placed in the nickel deposition solution, and the electrochemical nickel plating is performed in three stages: in the first stage, an oxidation current of 1-2 mA is passed for a duration of 0.5-1.5 h; in the second stage, an oxidation current of 2.5-3.5 mA is passed for a duration of 1-3 h, and in the third stage, an oxidation current of 4-6 mA is passed for a duration of 1-3 h; after the three stages, a uniform nickel layer is deposited on the surface of the PMMA complementary structure with the silver layer, the nickel layer is tightly combined with the structure to form the nickel-complementary structure composite.

8. The method of claim 1 or 7, wherein the nanostructure-based high-hardness nickel imprint template is prepared by the steps of: (a) preparing a nickel film on a substrate; (b) preparing a nanostructure on the nickel film; (c) preparing a nanostructure-based high-hardness nickel imprint template by etching the nickel film. The nickel deposition solution comprises nickel sulfate hexahydrate, nickel chloride hexahydrate and boric acid.

9. A high-hardness nickel imprinting mold prepared by the preparation method in any one of claims 1-8.

10. Use of the high-hardness nickel imprinting mold in claim 9 in nanoimprinting and micro-nano device manufacturing.